Odpowiedzi

2010-02-25T19:09:30+01:00
A)12y-y-5=10y-1
y=4
b)2u-10+15=3u-12+10
-u=-7
u=7
c)-3y/3-3-2=4-4y
-y+4y=4+5
3y=9
y=3
d)6a-4-6=9a-4,5+0,5
-3a=-4+10
a=-2
5 3 5
2010-02-25T19:16:04+01:00
A)12y-(y+5)=10y-1
12y-y-5=10y-1
11y-5=10y-1
11y-10y=-1+5
y=4
b)2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u+5=3u-2
2u-3u=-2-5
-u=-7/:-1
u=7
c)-3(y/3+1)-2=4(1-y)
-y-3-2=4-4y
-y-5=4-4y
-y+4y=4+5
3y=9/3
y=3
d)2(3a-2)-6=4,5(2a-1)+1/2
5a-4-6=9a-4,5+1/2
5a-10=9a-4
5a-9a=-4+10
-4a=6/-4
a=-1,5
6 4 6
Najlepsza Odpowiedź!
2010-02-25T19:20:39+01:00
A) 12y-(y+5)+10y-1
12y-y-5=10y-1
12y-y-10y=-1+5
y+4

b) 12(u-5)+15=3(u-4)+10
12u-60+15=3u-12+10
12u-3u=10-12-15+60
9u=43/ :9
u=4 7/9 (cztery i siedem dziewiątych)

teraz bede pisać już odpowiedzi same :)

c) -3y/3 -3-2=4-4y / *3
-3y-9-6=12-12y
-3+12y=12+6+9
9y=27 / :9
y=3

d) 6a-4-6=9a-4,5+1/2 / *2
12a-8-12=18a-9+1
12a-18a=-9+1+12+8
-6a=12 / :(-6)
a= -2

Proszę :D

15 3 15